The Monstrous Mother - Limb, Stephanie (2025)
The Monstrous Mother is a research project that takes the form of a novel told through essays. It explores motherhood through an interplay of criticism, auto-theory, poetry and prose. It is a single, blended, creative-critical project where form plays an active part in the content. The narrative follows the early years of motherhood, when I struggled to reconcile what my role meant for and about my identity and body and I re-examined my relationship with different generations of mothers in my family. The research uncovers narratives of motherhood that challenge the ideal of the symbiotic mother-child couple. The story of Pasiphaë (and the Minotaur) recurs throughout. I ask: who is the ‘monster’, examining the term from multiple angles. Is it the mother, the child, or is it the labyrinth: the structures and systems that trap mother and child? ‘Monster’ derives from the same root word as demonstrate and before the birth of embryology, monstrous births were seen as portents. The essays also use monstrosity as a form of demonstration: by being candid about monstrous thoughts and acts. The research is interdisciplinary, encompassing medical humanities, literature, psychoanalysis, and contemporary culture. I am influenced by many writers who blend criticism with narrative, like Maggie Nelson in The Argonauts and Anne Carson in ‘The Glass Essay.’ I explore the martyrdom of early parenting, with reference to the submission of reading; reading pornography; the story of my sordid affair with a sixteenth century heretic/philosopher; my own experience of sex after giving birth; the history of teratology; and Kristeva’s theory of abjection. Ultimately, I examine how relationships are strained by the responsibilities that come with young children, asking how the individuals who make up a constellation called ‘the nuclear family’ function (and dysfunction). The essays travel through time, the imagination and the lived experience.